Design Optimization of Time-and Cost-Constrained Fault-Tolerant Distributed Embedded Systems - Izosimov, Viacheslav; Pop, Paul; Eles, Petru; Peng, Zebo (Design, Automation and Test in Europe, 2005)
In this paper we present an approach to the design optimization of fault-tolerant embedded systems for safety-critical applications.Processes are statically scheduled and communications are performed using the time-triggered protocol.We use process re-execution and replication for tolerating transient faults.Our design optimization approach decides the mapping of processes to processors and the assignment of fault-tolerant policies to processes such that transient faults are tolerated and the timing constraints of the application are satisfied.We present several heuristics which are able to find fault-tolerant implementations given a limited amount of resources.The developed algorithms are evaluated using extensive experiments, including a real-life example.